A high-fat high-sugar diet-induced impairment in place-recognition memory is reversible and training-dependent. (1st March 2017) - Tran, Dominic M.D.; Westbrook, R. Frederick
Abstract: A high-fat high-sugar (HFHS) diet is associated with cognitive deficits in people and produces spatial learning and memory deficits in rodents. Notable, such diets rapidly impair place-, but not object-recognition memory in rats within one week of exposure. Three experiments examined whether this impairment was reversed by removal of the diet, or prevented by pre-diet training. Experiment 1 showed that rats switched from HFHS to chow recovered from the place-recognition impairment that they displayed while on HFHS. Experiment 2 showed that control rats ("Untrained") who were exposed to an empty testing arena while on chow, were impaired in place-recognition when switched to HFHS and tested for the first time. However, rats tested ("Trained") on the place and object task while on chow, were protected from the diet-induce deficit and maintained good place-recognition when switched to HFHS. Experiment 3 examined the conditions of this protection effect by training rats in a square arena while on chow, and testing them in a rectangular arena while on HFHS. We have previously demonstrated that chow rats, but not HFHS rats, show geometry-based reorientation on a rectangular arena place-recognition task (Tran & Westbrook, 2015). Experiment 3 assessed whether rats switched to the HFHS diet after training on the place and object tasks in a square area, would show geometry-based reorientation in a rectangular arena. The protective benefit of training was replicated in the square arena, but both Untrained and Trained HFHS failed to show geometry-based reorientation in the rectangular arena. These findings are discussed in relation to the specificity of the training effect, the role of the hippocampus in diet-induced deficits, and their implications for dietary effects on cognition in people.